Repaying the debt: an examination of the relationship between perceived organizational support and unethical pro-organizational behavior by low performers - Wang, Xiaoyu (Journal of business ethics, 2022)
Drawing on social exchange theory, we examine the conditions under which employees’ good intentions motivate them to engage in unethical pro-organizational behavior (UPB) and the psychological mechanism behind this behavioral decision. Findings from a time-lagged field study and a scenario study indicate (1) an interactive effect between perceived organizational support and employee performance on UPB; (2) that low performers who perceive high levels of organizational support are more likely to engage in UPB; and (3) that feelings of indebtedness to the organization mediate the interactive effect on UPB. Therefore, the paper highlights the importance of conditional factors in motivating UPB by combining employee ‘good intentions’ and ‘disadvantageous situations’ to understand the UPB decision process. The paper concludes with theoretical and practical implications.